PENGARUH KOMPENSASI, PENGEMBANGAN KARIER, DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI BALAI PENGELOLAAN SUMBER DAYA AIR BENGAWAN SOLO - -, Waluyo (JI@P, 2015)
This study belongs to survey with quantitative approach. Researchsample was the entire employee in Resource Management Irrigate theBengawan Solo Office counted 92 people what is taken by total sampling.Data collection technique used questionnaires. Meanwhile, data wasanalyzed by using multiple linear regressions analyze.Result of analyze was tcount value for the compensation variable equal to3,499 > ttable (1,988) by sinificant (p value) equal to 0,001 < 0,05. Thismatter was mean compensation have an influence on positive towardemployee performance. While tcount value for the career developmentvariable equal to 2,517 > ttable (1,988) by significant (p value) equal to0,014 < 0,05. This matter was mean career development have aninfluence on positive toward employee performance, and then tcount valuefor the work satisfaction variable equal to 3,027 > ttable (1,988) by sigificant(p value) equal to 0,003 < 0,05. This matter was mean work satisfactionhave an influence on positive toward employee performance. Result ofanalyze F test was obtained Fcount value (21,720) > Ftable (3,10) bysignificant (p value) 0,000 < 0,05. This matter was mean compensation,career development and work satisfaction by simultaneous have aninfluence on positive toward employee performance.Based on the result analyze can conclusion that compensation, careerdevelopment and work satisfaction individually and simultaneous have aninfluence on positive toward employee performance of ResourceManagement Irrigate the Bengawan Solo Office. From the conclusion canbe suggested in order to partly of office in effort improve the employeeperformance, require to consider the aspect of Employee RepairSubssidy and Employee Old Day Subsidy, for career development needmore paying attention of employee aspect and for work satisfaction, theparty of office more paying attention of work kind having the character ofto challange for all employee.Key word: Compensation, Career Development, Work Satisfaction, EmployeePerformance